Et grafisk blad fra Lüneburg og dets brug i Danmark: - lidt fortsat forlægshistorie fra 1600-tallet - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 2009)
In Kirkehistoriske Samlinger 1992 I drew the attention to an epitaph in the parish church of Taulov near Fredericia in Eastern Jutland. The article pointed to a specific graphic source ofits motif: the frontispiece of C. Cassube’s complete hymnal of 1677. Since then the motif has been traced back to a more detailed print by H. Wierix of the Southern Netherlands. As to the origin ofCassube’s frontispiece and the one used in Nackskov’s Articles ofReligion of 1697 this new investigation points to the Lüneburg printing house of the Stern in Lüneburg, Germany. Here a book ofsermons by Theodor Steding of Schaumburg-Lippe was published in 1664 with a frontispiece quite similar to the Danish examples used by the Copenhagen printers Cassube and Bockenhoffer, though considerably more detailed. A new consideration makes it seem likely, that the Copenhagen printers have been copying the Lüneburg print with some significant alterations - such as the omission ofthe quotations ofthe Bible. This may have caused the painter ofTaulov to interpret the figure of Paul as Moses. The theme ofthe print is not man between law and grace, but the liberation of the Old Adam from the weight of original sin and the future perspective ofthe new life in Christ.